2011
DOI: 10.1089/cyber.2009.0187
|View full text |Cite
|
Sign up to set email alerts
|

Virtual/Real Transfer of Spatial Knowledge: Benefit from Visual Fidelity Provided in a Virtual Environment and Impact of Active Navigation

Abstract: The purpose of this study was to evaluate the effect the visual fidelity of a virtual environment (VE) (undetailed vs. detailed) has on the transfer of spatial knowledge based on the navigation mode (passive vs. active) for three different spatial recall tasks (wayfinding, sketch mapping, and picture sorting). Sixty-four subjects (32 men and 32 women) participated in the experiment. Spatial learning was evaluated by these three tasks in the context of the Bordeaux district. In the wayfinding task, the results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(83 citation statements)
references
References 35 publications
4
79
0
Order By: Relevance
“…All of the material and procedures are derived from previous studies demonstrating the relevance of VR-based applications to study spatial learning (Wallet, Sauzéon, Rodrigues, & N'Kaoua, 2008;Wallet, Sauzéon, Rodrigues, Larrue, & N'Kaoua, 2009;Wallet, Sauzéon, Rodrigues, Larrue, & N'Kaoua, 2010;Wallet, Sauzéon, Pala, Larrue, & N'Kaoua, 2011). The VE was a replica of the district near Bordeaux's hospital.…”
Section: Vr-based Materials and Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…All of the material and procedures are derived from previous studies demonstrating the relevance of VR-based applications to study spatial learning (Wallet, Sauzéon, Rodrigues, & N'Kaoua, 2008;Wallet, Sauzéon, Rodrigues, Larrue, & N'Kaoua, 2009;Wallet, Sauzéon, Rodrigues, Larrue, & N'Kaoua, 2010;Wallet, Sauzéon, Pala, Larrue, & N'Kaoua, 2011). The VE was a replica of the district near Bordeaux's hospital.…”
Section: Vr-based Materials and Proceduresmentioning
confidence: 99%
“…If the subject made a wrong decision, he was shown the correct direction by the experimenter and continued on the route. Thus, two scores were calculated from this task: the number of direction errors (wrong turns) and the number of stops during the wayfinding task, as a probe of the use of spatial representation to perform a navigational task (Lapeyre, Hourlier, Servantie, N'Kaoua, & Sauzéon, 2011;Wallet et al, 2008Wallet et al, , 2009Wallet et al, , 2010Wallet et al, , 2011.…”
Section: Wayfinding Taskmentioning
confidence: 99%
See 1 more Smart Citation
“…Different authors already showed great spatial transfers with "normal" [1][2] [3] or patients with disabilities people [27]. Numerous factors like visual fidelity [2], retention delay [1], game experience [16] [24]. Moreover, these interfaces don't provide vestibular information, known to improve spatial acquisition.…”
Section: Spatial Cognition and Spatial Transfer From Virtual To Real mentioning
confidence: 99%
“…These results are in accordance with literature. For example, Wallet et al [2] found, on the same type of task, that visual fidelity of a VE was more important than the interface used. We may wonder that different body-based information and attentional levels provided by our four interfaces had a little impact on tasks that do not require the recall of an action.…”
Section: Egocentric Tasksmentioning
confidence: 99%